Meranzin hydrate from Muraya paniculata - Julaeha, E.; Supratman, U.; Mukhtar, M.R.; Awang, Khalijah; Ng, S.W. (International Union of Crystallography, 2010)
The coumarin ring system in the title compound, C15H18O5 [IUPAC name: 8-(2,3-dihydroxy-3-methylbutyl)-7-methoxy-2H- 1-benzopyran-2-one], isolated from Muraya paniculata, is planar (r.m.s. deviation 0.017 angstrom). In the crystal, the two hydroxy groups are involved in O-H center dot center dot center dot O hydrogen bonding with adjacent molecules, forming a sheet structure.